Identification of factors towards contributing frequency of walking to access urban rail transit station - Jaafar Sidek, Mohd Farid; Kadar Hamsa, Abdul Azeez; Hj. Mohd. Noor, Norzailawati; Ibrahim, Mansor (Eastern Asia Society for Transportation Studies, 2019)
Traffic congestion has been worsening in a car-dependency city during morning and evening peak hours. Thus, urban rail transit is one of the alternatives that can be adequately considered in addressing the tremendous increase in travel demand due to its exclusive right of way. The purpose of this paper is to identify the factors which contribute to the frequency of walking to access urban rail transit station. Three respective Light Rail Transit (LRT) stations at Kelana Jaya and Ampang lines were selected in Greater Kuala Lumpur (GKL). A set of questionnaire consist of trip-maker and trip-making characteristics, as well as perception on walking to LRT stations, were distributed to the respondents who access the LRT stations by walking. Frequency distribution, correlation, Relative Importance Index (RII), and Binary Logistic Regression were used to analyze the findings.